Lung cancer among textile workers in the Prato area of Italy. - Zappa, Marco; Paci, E.; Seniori Costantini, Adele; Kriebel, David (Scandinavian Journal of Work, Environment & Health, 1993)
The association between lung cancer and occupational exposure in the textile industry was investigated in a population-based case-referent study conducted in the Prato area of the province of Florence (Italy) where there is a concentration of textile factories. A complete response to a postal questionnaire was obtained for 207 cases (85.1%) and 440 referents (76.1%). Those who had ever worked in the textile industry had an odds ratio (OR) of 1.45 [95% confidence interval (95% CI) 1.0-2.1]; when nine different textile job titles were considered, an increased OR was observed only for rag sorters (OR 2.2, 95% CI 1.3-3.8) and weavers (OR 1.7, 95% CI 1.1-2.7). Analysis by different ``time windows'' showed an OR of 3.0 (95% CI 1.6-5.8) for rag sorters at work in the 1950s and an OR of 2.8 (95% CI 1.5-5.0) for weavers at work in the 1970s. This result supports the suggestion of two different carcinogenic exposures in the Prato textile industry (asbestos and mineral oils).